The Study of Renaissance and Reformation Books on the Canadian Prairies - Watt, David; Wright, Sharon; Dyck, Paul (Renaissance and Reformation / Renaissance et Réforme, 2014)
This article begins by providing a survey of collections holding Renaissance and Reformation books in Saskatchewan and Manitoba in order to draw attention to the range of resources across the prairies. The article’s second section focuses on the manuscripts and rare books at the University of Manitoba in order to highlight the research opportunities afforded by individual collections and the potential benefits of exploring them in aggregate. Taken together, the collections described here—from the bibles donated by Rev. Greatorex to St. John’s College in 1897 to the remarkable collection of early books at Notre Dame College in Wilcox, Saskatchewan—can help us to consider questions about the cultural and physical place of books in Reformation and Renaissance studies as well as questions about the significance of their place on the prairies.